2022
DOI: 10.3390/su14052516
|View full text |Cite
|
Sign up to set email alerts
|

Project Governance and Project Performance: The Moderating Role of Top Management Support

Abstract: Project governance (PG) has been primarily acknowledged as critical by researchers and practitioners in regard to successfully executing projects. However, project governance of public projects has received less attention from researchers. Therefore, in this study, we studied the effects of project governance and top management support (TMS) on project performance (PP) and their interactions in public sector projects. Using the lens of resource dependence theory (RDT), we hypothesize whether TMS moderates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…Sometimes high-level planning or assistance is sufficient for the project’s success, but TMS is nearly always vital for the project’s success (Young & Poon, 2013). Project results depend on TMS, and it has been repeatedly found that TMS contributes significantly to the PS (Cooke-Davies, 2002; Davis, 2019; Fareed & Su, 2022a; Iyer & Jha, 2005; Mir & Pinnington, 2014; Pacagnella et al, 2019). Hence, we hypothesize that…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes high-level planning or assistance is sufficient for the project’s success, but TMS is nearly always vital for the project’s success (Young & Poon, 2013). Project results depend on TMS, and it has been repeatedly found that TMS contributes significantly to the PS (Cooke-Davies, 2002; Davis, 2019; Fareed & Su, 2022a; Iyer & Jha, 2005; Mir & Pinnington, 2014; Pacagnella et al, 2019). Hence, we hypothesize that…”
Section: Literature Reviewmentioning
confidence: 99%
“…The top management has a critical part in facilitating and supplying the resources necessary for project success (Fareed & Su, 2022a; Staehr, 2010). Various researchers have established the significance of TMS for the information systems PS (Ayat et al, 2021; Boonstra, 2013; Dwivedi et al, 2013; Zwikael, 2008); the recommendation in the prior research is to secure TMS for the projects to ensure a safe path to success.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This support forms the basis of effective communication and ensures the smooth passage of necessary changes [7]. In addition, the role of top management includes impact on organizational culture and performance, being a key element in risk management and project governance [4] [8]. This support is also a driver of change toward sustainable practices in construction projects and sustainable housing success [5] [9], while mediating and moderating the relationship between technology implementation and performance, as investigated by [10].…”
Section: Top Management Supportmentioning
confidence: 99%
“…The environmental identity of TMT is the extent to which the TMT's self-conceptualizes toward the environment, and a TMT who has a high level of environmental identity will affect a company's strategic choice [38]. In addition, based on upper echelons theory [39], a TMT's decision-making processes are caused by supervisors' characteristics, and leadership is a key characteristic of a supervisor [40][41][42][43], supporting the mediating role of environmental identity. Indeed, as discussed above, sustainable leadership promotes the environmental identity of the TMT, and the environmental identity of the TMT will influence a company's strategic choice.…”
Section: The Mediating Role Of the Environmental Identity Of The Tmtmentioning
confidence: 99%